The Potential Benefit of Three vs. Six Cycles of Carboplatin, Etoposide, and Vincristine in Postenucleation High-Risk Patients with IRSS Stage I Retinoblastoma. (1st November 2016) - Ye, Huijing; Du, Yi; Chen, Rongxin; Luo, Xin; Mao, Yuxiang; Ai, Siming; Ma, Wenfang; Ding, Yungang; Li, Qian; Yang, Huasheng
ABSTRACT: Purpose : To compare the clinical effects of different cycles of carboplatin, etoposide, and vincristine (CEV) regimens of adjuvant chemotherapy in postenucleation high-risk patients with IRSS Stage I retinoblastoma (RB). Methods : A retrospective analysis of 53 RB patients hospitalized in the Zhongshan Ophthalmic Center of Sun Yat-sen University was performed. All patients had unilateral involvement, received enucleation treatment, were diagnosed as RB by pathology, and had high-risk pathological factors. Patients either refused postoperative chemotherapy or received three or six cycles of CEV regimen chemotherapy. The clinical information, treatment, and results of patients in all groups were compared. Results : A total of 19 cases refused postenucleation chemotherapy, 18 cases received three cycles, and 16 cases received six cycles of the CEV regimen chemotherapy. The 5-year disease-free survival rate and the overall survival (OS) rate in the chemotherapy group were higher than those in the non-chemotherapy group (97.1% vs. 63.2%, p = 0.001) and were not different between the three-cycle chemotherapy group and the six-cycle chemotherapy group (94.4% vs. 100%, p = 0.35). Conclusion : After eye enucleation for patients with high-risk unilateral RB, the CEV regimen chemotherapy was associated with a higher survival rate. The three-cycle CEV regimen adjuvant chemotherapy was effective and is expected to replace the six-cycle CEV regimen chemotherapy.